The falcon's feathers - Roy, Ron; Gurney, John Steven (New York : Random House, 1998)
Josh and his two friends look for the person who stole a peregrine falcon from its nest.
"A Stepping Stone book."
Keywords: Peregrine falcon; Falcons; Mystery and detective stories